Implementation of the Hanura Take Away Application and Insta 360o Tourism in Hanura Pesawaran Village, South Lampung - Debby Alita; Imam Ahmad; Emi Suwarni; Asmawati Asmawati (STKIP Singkawang, 2022)
The world of industry and education are asked to move forward and cooperate in developing technology. Hanura Village is a district in Lampung Province that has not implemented technology to the fullest because none of the gojek and online transportation services have yet entered this area. In 2019 it coincided with the covid pandemic that occurred in Indonesia and demanded the community to carry out PPKM so that people were restricted from traveling outside the home. Hanura take away is a solution for MSMEs and residents of Hanura who carry out product sales and purchase transactions and place orders for tourism tickets with image facilities using Insta 360o in the Hanura area of Pesawaran. This application is considered and considered very good for the local community because it makes it easier to make transactions in the Hanura village and makes it easier for other people to order tourist tickets as evidenced by the success of consumers and MSMEs in buying and selling activities.